Investigation of Waveguide Propagation of Terahertz Signal with Different Polarization Angle and Twisting Rate for Terabit DSL Application - Syahnon, Muhamad Syahrieza; See Khee, Dr. Yee; Che Seman, Fauziahanim; Ahmad, Arslan (Journal of Electronic Voltage and Application, 2022)
When the demand for higher data rates grows, various telecommunications technologies are proposed; for these cases, the terabit DSL is investigated. Terabit DSLs provides solutions to the inevitable bottleneck that future wireless systems encounter. However, the propagation loss in twisted pairs becomes a massive concern in terabit DSL. Besides the attenuation, propagation characteristics at terahertz frequencies in twisted pair are not much explored by the researcher. Therefore, terahertz signal propagation characteristics in a waveguide based on surface plasmonic are investigated in this project by using simulation software CST MICROWAVE STUDIO. A circular waveguide with radius of 0.25 mm and length of 20 mm respectively has been simulated in between 360 GHz to 380 GHz. The reflection coefficient and transmission coefficient analysis of the circular waveguide are investigated in terms of the polarization angles and twisting rate. Based on the simulated results, it is discovered that the polarization angle influences the reflection coefficient and transmission coefficient of the circular waveguide. When the polarization angle difference is 90 degrees, it has the worst reflection. The circular waveguide with a polarization angle difference of 0 degrees and 180 degrees, it has the best transmission coefficient. The transmission coefficient of the circular waveguide, on the other hand, is unaffected by the twisting rate. Even though the highest twisting rate that has the highest transmission coefficient, it is still lower than 3 dB. Besides, the higher the twisting rate the lesser the number of resonances for the circular waveguide.